IMF Committee on Balance of Payments Statistics : Annual Report 2016. (Balance of Payments Statistics; Balance of Payments Statistics, 2017)
The 2016 Annual Report of the IMF Committee on Balance of Payments Statistics (Committee) provides an overview of recent trends in global balance of payments and international investment position (IIP) statistics, summarizes the Committee's work program during 2016, and presents the work program of the Committee in the coming year.